The Influence of Noice Levels in The Cabin Tower on The Work Environment of Air Traffic Controllers at Airnav Indonesia Subranch Gorontalo - Krisman, Muhammad Rafli; Putriekapuja, Rany Adiliawijaya; Amir, Elfi (Kontribusia : Research Dissemination for Community Development, 2024)
This study was conducted at the Perum LPPNPI Branch Office in Gorontalo, Gorontalo Province, from January to June 2024. The background of this research is the inadequate condition of the cabin tower and substandard communication equipment, which disrupt the performance of Air Traffic Controllers (ATC). The aim of this study is to determine the impact of noise in the cabin tower on the working environment of ATC. It is hoped that this research will provide solutions to the noise impact and help ATC achieve a compliant and comfortable working environment for providing air traffic services. The method used is quantitative. Data collection involved using a Likert scale questionnaire and direct noise measurement with a sound level meter, specifically the Uni T - UT 353 model. Data analysis was performed using Pearson's Product-Moment Correlation, coefficient tests, and regression. The study population consisted of 8 ATC personnel at the AirNav Tower unit in Gorontalo. The results showed a strong correlation between noise in the cabin tower and the ATC working environment, with a correlation coefficient of 0.823 and a determination coefficient of 67%. This means that noise affects the working environment by 67%, while the remaining 33% is influenced by other factors not examined. These findings emphasize the importance of addressing noise issues to enhance ATC performance and work comfort.